Chair's note: opening access to our resources and our research. (15th October 2018) - Atkinson, David
Abstract: This second annual note on the Society's activities outlines how we have responded to the ongoing crisis in Libya and our connected inability to work in the region by developing our research activities and facilities in the UK. Our most advanced initiative is our project to catalogue the Society's archive and makes its contents available online. Similarly, we are exploring how we might promote our library and encourage greater awareness and use of this unique resource. Finally, we are providing an increasing range of our books and field reports in Open Access formats via our website. All of this aims to make our distinctive resources more easily available to members, and to wider research communities in the UK and overseas. Abstract : هذه الملاحظة السنوية الثانية عن أنشطة الجمعية تضع الخطوط العريضة عن كيفية استجابتنا للأزمة المستمرة في ليبيا و ما نجم عنها من عجزنا عن العمل في المنطقة، وذلك من خلال تطوير النشاطات والمرافق البحثية لدينا هنا في المملكة المتحدة. المبادرة الأكثر تقدما لدينا هي مشروع تصنيف أرشيف الجمعية وجعل محتوياته متاحة على الإنترنت. وبالمثل، فنحن نقوم بالبحث عن كيفية الترويج لمكتبتنا لتحقيق وعي أكبر واستخدام أكثر لهذا المورد الفريد. وأخيرا ،فنحن نقوم بتقديم مجال متزايد من كتبنا وتقاريرنا الميدانية في تنسيقات الوصول المفتوح (Open Access) عبر موقعنا الالكتروني . كل هذا يهدف إلى جعل مواردنا المميزة متاحة بسهولة أكبر للأعضاء والمجتمعات البحثية على نطاق أوسع في المملكة المتحدة وخارجها.